The relationship between body mass index and body image in Brazilian adults - Idalina S. Kakeshita (Psychology & Neuroscience, 2008)
The aim of this work was to assess the relationship between nutritional status and body image perception in Brazilian adults. Participants included 280 adults (18-60 years) of both genders. The sample was composed proportionally to the Brazilian nutritional status distribution according to body mass index, with volunteers of all economic classes and educational levels. We applied a Figure Rating Scale to examine body image concerning size and shape. Both men and women were dissatisfied with their body size. Regarding body discrepancy, eutrophic adults overestimated their body size and desired leaner bodies. Our results also showed that the higher the BMI, the smaller the differences between men and women. These findings reinforce that body image perception is an important factor to be considered by health professionals in order to improve quality of life.